Effect of L-carnosine on frozen ram-semen quality evaluated by CASA and flow-cytometry - Gungor, Ibrahim Halil; Gur, Seyfettin; Guler Ekmen, Edanur (Csiro Publishing, 2024)
Context Successful freezing of ram semen has not yet reached the desired levels. The main reason for this situation could be due to the fact that the spermatozoa of this species have a lipid composition different from that of other species.Aims The objective of the study was to evaluate the effect of different concentrations of L-carnosine added to the extender on ram semen after being frozen and thawed.Methods Semen was collected from six Akkaraman rams twice a week for a period of 3 weeks. Pooling was performed at each time. The semen were reconstituted with a pre-prepared tris + egg yolk solution and different amounts of L-carnosine to form experimental groups (Group 1: 1 mM, Group 2: 5 mM, Group 3: 10 mM, Group 4: 20 mM, Group 5: control) and were drawn into 0.25 mL mini straws. Subsequently, the samples were subjected to freezing by using an automated freezing device. Following the freezing process, the straws were placed in containers containing liquid nitrogen and thawed after 24 h.Key results After thawing, it was found that the samples containing 5 mM L-carnosine had superior results in all analyses. This concentration exhibited significantly higher percentages of progressive, total, and rapid sperm motility, live spermatozoa, high mitochondrial membrane potential rate, and higher GSH-Px concentrations. In addition, it was determined that 5 mM L-carnosine group protected the membrane integrity and significantly decreased the rate of abnormal spermatozoa, acrosomal damage rate, low mitochondrial membrane potential and apoptotic cell rate.Conclusions As a result, It was determined that adding 5 mM of L-carnosine to the semen extender during the freezing of ram samples would be beneficial for successful freezing.Implications The addition of 5 mM L-carnosine to ram-semen extenders ensures the freezability of the semen of this species; thus, this protocol could be used to perform artificial insemination with frozen ram semen. In this study, L-carnosine was added to semen diluents so as to overcome the problems encountered during the freezing of ram semen. The cell membrane protecting and diluent pH buffering properties of L-carnosine came to the fore. The freezing quality of semen was found to be enhanced when 5 mM of L-carnosine was added. This result was demonstrated by basic analyses (computer-assisted semen analysis (CASA) and flow-cytometry) of ram semen after freezing and thawing.
Keywords: apoptosis; flow-cytometer; freeze-thawing; L-carnosine; oxidative stress; pH; ram; semen